The Inspiration and Truth of Sacred Scripture : The Word that Comes from God and Speaks of God for the Salvation of the World - O'Fearghail, Fearghus; Gregg, Stephen, O.Cist; Esposito, Thomas (Book collections on Project MUSE., 2014)
In his 2009 post-synodal apostolic exhortation Verbum Domini, Pope Benedict XVI pointed out that "theological reflection has always considered inspiration and truth as two key concepts for an ecclesial hermeneutic of the sacred Scriptures" and that there is today the need "for a fuller and more adequate study of these realities, in order to better respond to the need of interpreting the sacred texts in accordance with their nature." The Inspiration and Truth of Sacred Scripture: The Word That Comes from God and Speaks of God for the Salvation of the World is the contribution of the Pontifical Biblical Commission toward a more adequate understanding of the concepts of inspiration and truth that respects both the nature of the Bible and its significance for the life of the Church. Drawing on a close reading of the Scriptures themselves, the document focuses on three main aspects: 1. The inspiration of Sacred Scripture and the exploration of its divine provenance 2. The truth of the Word of God, emphasizing the message about God and his project of salvation 3. Challenges that arise from the Bible itself, on account of certain aspects that seem inconsistent with its quality of being the Word of God Reading this document, formally approved by Pope Francis, will strengthen the reader to receive the word of God-in the liturgical assembly and in every other place-in its theological, Christological, soteriological, and ecclesiological context in a way that corresponds ever more closely to this unique gift of God whereby God communicates his very self and invites us into communion with him.